2019
DOI: 10.22146/majkedgiind.39164
|View full text |Cite
|
Sign up to set email alerts
|

Differences between male and female mandibular length growth according to panoramic radiograph

Abstract: Evaluation of the mandible was used for age and sex determination in the forensic field and it established the treatment planning in dentistry. The present study aims to determine mandibular length growth on male and female group aged   9-25 years old using panoramic radiograph. The research was conducted using analytical cross-sectional design method. The subject of this research was 412 panoramic radioraphs of patients aged 9-25 years old. It involved a totalsamples of 207 males and 205 females. This researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…These findings are consistent with the study by Azhari et al, which also demonstrated no significant difference in mandibular cortex width values between males and females. 15 The findings of this study are consistent with the research conducted by Satria et al, which also demonstrated a decrease in mandibular cortical thickness in hypertensive patients consuming amlodipine.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with the study by Azhari et al, which also demonstrated no significant difference in mandibular cortex width values between males and females. 15 The findings of this study are consistent with the research conducted by Satria et al, which also demonstrated a decrease in mandibular cortical thickness in hypertensive patients consuming amlodipine.…”
Section: Discussionsupporting
confidence: 93%
“…20 The results of this study are supported by the research conducted by Azhari et al in 2019, which stated that there were relatively small differences in the average length of the right and left mandibles between males and females. 15…”
Section: Discussionmentioning
confidence: 99%
“…In the age group of 20-24 year, it presents the decrease of the mandibular growth. Meanwhile, the age group of 25-29 years indicates that the mandibular size is relatively constant [12,13]. From the table, it shows that most of the subjects were from the age 2 and 3 show the distribution of the position of the mandibular foramen in each age group based on the side of the mandibular foramen studied.…”
Section: Resultsmentioning
confidence: 99%
“…It can be caused by the increase in the mandible length and width that occurs with increasing age [8]. Thus, the sample grouping in this study was based on the age of mandibular development to facilitate researchers in describing the position of the mandibular foramen according to age [12,13]. A total of 330 panoramic radiographs were used as samples in this study consisting of 34 radiographs of patients aged 10-14 years, 49 radiographs of patients aged 15-19 years, 187 radiographs of patients aged 20-24 years, and 60 radiographs of patients aged 25-29 years.…”
Section: Discussionmentioning
confidence: 99%
“…2 B). The acceleration of mandibular growth takes place together with the growth of body height, which peaks at the age of 12–14 years in female [ 15 , 16 ]. Besides, children are generally uncooperative or disobey with post-operative instructions.…”
Section: Discussionmentioning
confidence: 99%